Music and Translation New Mediations in the Digital Age - Desblache, Lucile; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book explores how transformations and translations shape musical meanings, developments and the perception of music across cultures. Starting with the concept of music as multimodal text, the author understands translation as the process of transferring a text from one language - verbal or not - into another, interlingually, intralingually or intersemiotically, as well as the products that are derived from this process. She situates music and translation within their contemporary global context, examining the tensions between local and global, cosmopolitan and national, and universal and specific settings, to arrive at a celebration of the translational power of music and an in-depth study of how musical texts are translated. This book will be of interest to translation studies scholars who want to broaden their horizons, as well as to musicians and music scholars seeking to understand how cultural exchange and dissemination can be driven by translation. Lucile Desblache is Professor of Translation and Transcultural Studies at the University of Roehampton, UK. She studied both musicology and comparative literature. This is reflected in her research interests which are twofold: the representation of the non-human in contemporary cultures on the one hand, and the translation of musical texts on the other. .
Chapter 1: Prelude -- Part 1: Music and translation in a global context -- Chapter 2: Music, centres and peripheries -- Chapter 3: Music and translation today -- Part 2 Translating music -- Chapter 4: What is translated? Styles, genres, rhythms and more -- Chapter 5: What is translated? Vocal music, voice and more -- Chapter 6: How is music translated? Mapping the landscape of music translation -- Part 3: Music translates -- Chapter 7: Music and human activities -- Chapter 8: In and beyond the material -- Chapter 9: Music and the natural world -- Chapter 10: Coda. .
Keywords: Translating and interpreting; Music; Comparative literature; Language and languages -- Style; Language Translation; Music; Comparative Literature; Stylistics